Biphenyl bridge type thermoplastic polyesterimide, preparation method thereof, biphenyl bridge type thermoplastic polyesterimide film and application of biphenyl bridge type thermoplastic polyesterimide film
By adopting biphenyl bridge thermoplastic polyesterimide film, the performance challenges of the two layers of adhesive-free flexible copper clad plates are solved, and the comprehensive optimization of fluorine-free materials in terms of low dielectric constant, low dielectric loss, low water absorption, high thermal stability and adhesion are achieved.
Patent Information
- Application Number
- CN202411992300.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the development of two layers of adhesive-free flexible copper clad plates (FCCLs), it is difficult to meet performance requirements such as low dielectric constant, low dielectric loss, low water absorption, high thermal stability and good adhesion with copper foils at the same time, especially when fluorine-containing materials are not used.
Biphenylbridge thermoplastic polyesterimide (PEsI) film is used, which is prepared by polymerization and thermal imidation reactions of biphenylbenzoate-3,3’,4,4’-tetracarboxylic dianhydride, 3,3’,4,4’,-biphenyltetracarboxylic dianhydride and 2-(4-aminobenzoate)-5-aminobenzoate, which has excellent thermoplasticity, high temperature dimensional stability and dielectric properties.
The fluorine-free biphenyl-bridge thermoplastic polyesterimide film has a linear thermal expansion coefficient close to that of copper foil, excellent thermoplasticity, high temperature dimensional stability and dielectric properties, and is suitable for insulating polymer materials of two layers of flexible copper clad plates.
Smart Images

Figure BDA0005223905730000031 
Figure BDA0005223905730000032 
Figure BDA0005223905730000033
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermoplastic polyester imide, and specifically relates to a biphenyl bridge type thermoplastic polyester imide and a preparation method thereof, a biphenyl bridge type thermoplastic polyester imide film and an application thereof. Background Art
[0002] Flexible copper clad laminate (FCCL) is a plate-like base material for connecting circuit boards and transmitting signals in flexible printed circuit boards (FPCB). It is frequently used in electronic devices such as mobile phones, tablet computers, and laptops due to its excellent characteristics such as flexibility, thin thickness, light weight, and high conductivity.
[0003] FCCL is mainly composed of conductor (such as copper foil layer) and high molecular insulating polymer material. The signal transmission speed is related to the dielectric constant (D k ) and dielectric loss (D f ), so in order to obtain faster transmission speed, high molecular insulating polymers need to move towards low D k , low D f , low water absorption and high thermal stability.
[0004] Polyimide (PI) can not only meet these requirements, but also has the advantages of rigid imide ring structure, high temperature and low temperature resistance and radiation, good mechanical properties, flexible molecular designability, etc., so it has become a widely used high molecular insulating polymer in FCCL. However, due to the smooth surface and low roughness of PI, the film peeling strength generated directly by heat bonding of the copper foil layer and PI is low. Therefore, adhesives are generally used or PI is modified and designed during the production process to increase the adhesion between the high molecular insulating polymer and the copper foil layer. Among them, the presence of adhesives makes FCCL have problems such as poor thermal stability, large dielectric loss, and high porosity. Therefore, the two-layer adhesive-free FCCL is more concerned.
[0005] In the design scheme for modifying PI, in order to improve the dielectric properties, the introduction of low molar polarized fluorine-containing groups is a popular method. For example, the Chinese patent with the authorization publication number CN115850699B discloses a method for preparing a low dielectric blended polyimide. The technical scheme is through the blending of polyamic acid prepared by diamine containing thianthrene structure and ester bond, fluorine-containing diamine and fluorine-containing dianhydride monomer, respectively, and the good affinity of sulfide bond with metal is used to improve the adhesion of polyimide to metal copper. At the same time, the rigid and planar structure introduced can improve the thermal stability of polyimide, reduce its thermal expansion coefficient, and combine with ester bond to enhance the intermolecular force of polyimide, reduce the thermal expansion coefficient of polyimide. The blended polyimide prepared by the polymerization and blending of three monomers in the technical scheme has low dielectric constant, low thermal expansion coefficient and high thermal stability, which solves the problems of high and unstable dielectric constant and high thermal expansion coefficient of polyimide at low frequency.
[0006] The Chinese patent with the authorization publication number CN111484616B discloses a polyimide composition, a polyimide, a flexible copper-clad laminate and a method for making the same. The polyimide composition includes a diamine monomer, a dianhydride monomer and a solvent, the weight ratio of the diamine monomer to the dianhydride monomer is 1.4 to 1.6:1, and the diamine monomer includes 2,2'-bis(trifluoromethyl)benzidine and 2,2'-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane. The technical solution selects diamine monomers with flexible functional groups and dianhydride monomers for imidization. On the basis of maintaining the original low dielectric properties of the polyimide, the obtained polyimide has high flexibility, low hygroscopicity, heat resistance, and strong peel strength with copper foil. The peel strength of the obtained polyimide and copper foil is above 7.0N / cm after testing.
[0007] However, fluorine-containing materials are subject to significant restrictions on use due to defects such as biological toxicity. It is of great significance to develop a fluorine-free, two-layer adhesive-free FCCL that can be used in high-frequency conditions.
[0008] Polyesterimide (PEsI) is considered to have good application prospects in two-layer FCCLs because of its advantages such as good thermal stability, low water absorption, excellent dielectric properties, and low curing temperature compared to PI containing other chemical bonds. However, in order to meet the more stringent performance requirements in the FCCL field, PEsI needs to have good thermoplasticity, high temperature resistance, thermal conductivity, low dielectric constant, low dielectric loss, and good adhesion to copper foil.
[0009] Therefore, how to improve PEsI through modification and obtain PEsI films with good performance in all aspects has become a hot topic in the field of two-layer FCCL. Summary of the invention
[0010] In view of the above problems, the present invention provides a biphenyl bridge thermoplastic polyester imide and a preparation method thereof, a biphenyl bridge thermoplastic polyester imide film and an application thereof. The biphenyl bridge thermoplastic polyester imide provided by the present invention does not contain fluorine and has a linear thermal expansion coefficient close to that of copper foil, as well as excellent thermoplasticity, high temperature dimensional stability and dielectric properties.
[0011] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0012] The first aspect of the present invention provides a biphenyl bridge thermoplastic polyester imide, which is polymerized from biphenyl dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, 3,3',4,4',-biphenyltetracarboxylic dianhydride and 2-(4-aminobenzoate)-5-aminobiphenyl; the structural formula is shown in formula (I):
[0013]
[0014] (I); wherein m represents the mole number of biphenyl dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, m is an integer from 0 to 100, and m may be 0; n represents the mole number of 3,3',4,4',-biphenyltetracarboxylic dianhydride, n is an integer from 0 to 100, and n is not 0.
[0015] The structural formula of biphenyl dibenzoate-3,3',4,4'-tetracarboxylic dianhydride (BPTME) is as follows:
[0016]
[0017] The structural formula of 3,3',4,4',-biphenyltetracarboxylic dianhydride (BPDA) is as follows:
[0018]
[0019] The structural formula of 2-(4-aminobenzoate)-5-aminobiphenyl (ABABP) is as follows:
[0020]
[0021] Preferably, the ratio of m to n is 0-40:60-100.
[0022] The second aspect of the present invention provides a method for preparing the above-mentioned biphenyl bridged thermoplastic polyester imide, comprising the following steps:
[0023] (1) Under nitrogen protection, biphenyl dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride and 2-(4-aminobenzoate)-5-aminobiphenyl undergo polymerization reaction in a solvent to obtain a polyamic acid (PAA) solution;
[0024] (2) The polyamic acid solution is subjected to thermal imidization to obtain biphenyl bridged thermoplastic polyester imide.
[0025] Preferably, the total molar ratio of the 2-(4-aminobenzoate)-5-aminobiphenyl to the biphenyl dibenzoate-3,3',4,4'-tetracarboxylic dianhydride and 3,3',4,4',-biphenyltetracarboxylic dianhydride is 1:0.9-1.1, preferably 1:1.
[0026] Preferably, the thermal imidization adopts programmed temperature, and the programmed temperature steps are: 70-90°C for 0.5-1.5h, 110-130°C for 0.5-1.5h, 140-160°C for 0.5-1.5h, 170-190°C for 0.5-1.5h, 240-260°C for 0.5-1.5h, and 290-310°C for 0.5-1.5h.
[0027] Further preferably, the programmed temperature rising steps are: maintaining at 80°C for 1 hour, maintaining at 120°C for 1 hour, maintaining at 150°C for 1 hour, maintaining at 180°C for 1 hour, maintaining at 250°C for 1 hour, and maintaining at 300°C for 1 hour.
[0028] Preferably, the solvent is selected from at least one of N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), and dimethyl sulfoxide (DMSO).
[0029] More preferably, the solvent is N-methylpyrrolidone.
[0030] Preferably, the polymerization reaction is carried out at 5°C-35°C, and the reaction time is 20h-30h.
[0031] The third aspect of the present invention provides a biphenyl bridged thermoplastic polyester imide film, the composition of which includes the above-mentioned biphenyl bridged thermoplastic polyester imide.
[0032] Preferably, the linear thermal expansion coefficient of the biphenyl bridged thermoplastic polyester imide film is less than 26×10 -6 / K, glass transition temperature ≥230℃, dielectric constant <3.6, dielectric loss ≤0.005.
[0033] Preferably, the biphenyl bridged thermoplastic polyester imide film has a thickness of 0.03-0.05 mm.
[0034] The fourth aspect of the present invention provides the use of the biphenyl bridged thermoplastic polyester imide or the biphenyl bridged thermoplastic polyester imide film in the preparation of a two-layer flexible copper clad laminate.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The biphenyl bridge thermoplastic polyesterimide provided by the present invention uses diamine ABABP containing ester group and side benzene substituent, dianhydride BPTME containing ester group and biphenyl group, and dianhydride BPDA containing biphenyl group for polymerization reaction; the side benzene substituent increases the molar volume of the polyesterimide molecular chain, thereby reducing the dielectric constant and dielectric loss. At the same time, the presence of phenyl can adjust the rigidity of the molecule in the polyesterimide, and has good thermoplasticity and toughness; the biphenyl bridge thermoplastic polyesterimide has the characteristics of low water absorption, low dielectric constant, low dielectric loss, excellent thermal stability, good processing performance, etc. due to the ester group; the polyesterimide has good high temperature dimensional stability, good thermal stability and a linear thermal expansion coefficient similar to that of copper foil due to the rigid biphenyl group. Therefore, the biphenyl bridge thermoplastic polyesterimide film prepared by the preparation method provided by the present invention has the characteristics of a linear thermal expansion coefficient similar to that of copper foil, excellent thermoplasticity, high temperature dimensional stability and dielectric properties, so it can be used as an insulating polymer material in a two-layer flexible copper clad laminate. DETAILED DESCRIPTION
[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0038] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0042] In the following examples and comparative examples, unless otherwise specified, all raw materials used were commercially available or prepared by conventional methods in the art.
[0043] The structural formula of the monomer involved in the comparative example is as follows:
[0044]
[0045]
[0046] Example 1 Biphenyl bridged thermoplastic polyester imide film
[0047] (1) ABABP (15.2170 g, 50.0 mmol) and NMP (40.0 g) were added to a 250 mL three-necked glass bottle equipped with a mechanical stirrer, nitrogen inlet and outlet tubes, and a cold water bath; the reaction vessel was cooled to 10° C. using circulating cold water, and dry nitrogen was filled into the three-necked glass bottle. After stirring for 30 minutes, ABABP was completely dissolved in the solvent to obtain a reaction mixture; BPDA (14.7110 g, 50.0 mmol) and NMP (49.8 g) were added together. was added to the reaction mixture to obtain a polymerization system with a solid content of 25 wt%. After 1 h, when the initial heat of polymerization was released, the cold bath was removed and the reaction temperature naturally rose to room temperature. After 12 h, a uniform, transparent and viscous light brown PAA solution was obtained. The polymerization reaction was continued at room temperature for 24 h, and additional NMP (80.0 g) was added to dilute the PAA solution to 15 wt%. The PAA solution was filtered through a 0.45 μm Teflon syringe and the obtained PAA solution was stored in a refrigerator at -18°C.
[0048] (2) The PAA solution was cast on borosilicate glass (150 mm × 100 mm × 3 mm) using a film applicator (AFA-II, Shanghai Meiyu Equipment Co., Ltd., China), and the thickness of the liquid PAA film was adjusted to 0.04 ± 0.01 mm by a casting knife to obtain a coated glass substrate; the coated glass substrate was moved to a clean oven filled with dry nitrogen, and then thermal imidization was performed using a programmed temperature increase step of 80°C for 1 h, 120°C for 1 h, 150°C for 1 h, 180°C for 1 h, 250°C for 1 h, and 300°C for 1 h. After the temperature of the oven was cooled to room temperature, the coated glass substrate was immersed in deionized water, and the biphenyl bridged thermoplastic polyester imide film that was automatically peeled off was collected and dried at 120°C for 3 h.
[0049] Example 2 Biphenyl bridged thermoplastic polyester imide film
[0050] (1) ABABP (15.2170 g, 50.0 mmol) and NMP (40.0 g) were added to a 250 mL three-necked glass bottle equipped with a mechanical stirrer, nitrogen inlet and outlet tubes, and a cold water bath; the reaction vessel was cooled to 10° C. using circulating cold water, and dry nitrogen was filled into the three-necked glass bottle. After stirring for 30 minutes, ABABP was completely dissolved in the solvent to obtain a reaction mixture; BPTME (2.6722 g, 5.0 mmol) and BPDA (13.2399 g, 45.0 mmol) were added to the mixture. NMP (53.4 g) was added to the reaction mixture to obtain a polymerization system with a solid content of 25 wt%. After 1 h, when the initial heat of polymerization was released, the cold bath was removed and the reaction temperature naturally rose to room temperature. After 12 h, a uniform, transparent and viscous light brown PAA solution was obtained. The polymerization reaction was continued at room temperature for 24 h, and additional NMP (83.0 g) was added to dilute the PAA solution to 15 wt%. The PAA solution was filtered through a 0.45 μm Teflon syringe and the obtained PAA solution was stored in a refrigerator at -18°C.
[0051] (2) Same as step (2) of Example 1.
[0052] Example 3 Biphenyl bridged thermoplastic polyester imide film
[0053] (1) ABABP (15.2170 g, 50.0 mmol) and NMP (40.0 g) were added to a 250 mL three-necked glass bottle equipped with a mechanical stirrer, nitrogen inlet and outlet tubes, and a cold water bath; the reaction vessel was cooled to 10° C. using circulating cold water, and dry nitrogen was filled into the three-necked glass bottle. After stirring for 30 minutes, ABABP was completely dissolved in the solvent to obtain a reaction mixture; BPTME (5.3443 g, 10.0 mmol) and BPDA (11.7688 g, 40.0 mmol) were added to the mixture. ) and NMP (57.0 g) were added to the reaction mixture to obtain a polymerization system with a solid content of 25 wt%. After 1 h, when the initial heat of polymerization was released, the cold bath was removed and the reaction temperature naturally rose to room temperature. After 12 h, a uniform, transparent and viscous light brown PAA solution was obtained. The polymerization reaction was continued at room temperature for 24 h, and NMP (86.2 g) was added to dilute the PAA solution to 15 wt%. The PAA solution was filtered through a 0.45 μm Teflon syringe and the obtained PAA solution was stored in a refrigerator at -18°C.
[0054] (2) Same as step (2) of Example 1.
[0055] Example 4 Biphenyl bridged thermoplastic polyester imide film
[0056] (1) ABABP (15.2170 g, 50.0 mmol) and NMP (40.0 g) were added to a 250 mL three-necked glass bottle equipped with a mechanical stirrer, nitrogen inlet and outlet tubes, and a cold water bath; the reaction vessel was cooled to 10° C. using circulating cold water, and dry nitrogen was filled into the three-necked glass bottle. After stirring for 30 minutes, ABABP was completely dissolved in the solvent to obtain a reaction mixture; BPTME (8.0165 g, 15.0 mmol) and BPDA (10.2977 g, 35.0 mmol) were added to the mixture. ) and NMP (60.6 g) were added to the reaction mixture to obtain a polymerization system with a solid content of 25 wt%. After 1 h, when the initial heat of polymerization was released, the cold bath was removed and the reaction temperature naturally rose to room temperature. After 12 h, a uniform, transparent and viscous light brown PAA solution was obtained. The polymerization reaction was continued at room temperature for 24 h, and NMP (89.4 g) was added to dilute the PAA solution to 15 wt%. The PAA solution was filtered through a 0.45 μm Teflon syringe and the obtained PAA solution was stored in a refrigerator at -18°C.
[0057] (2) Same as step (2) of Example 1.
[0058] Example 5 Biphenyl bridged thermoplastic polyester imide film
[0059] (1) ABABP (15.2170 g, 50.0 mmol) and NMP (40.0 g) were added to a 250 mL three-necked glass bottle equipped with a mechanical stirrer, nitrogen inlet and outlet tubes, and a cold water bath; the reaction vessel was cooled to 10° C. using circulating cold water, and dry nitrogen was filled into the three-necked glass bottle. After stirring for 30 minutes, ABABP was completely dissolved in the solvent to obtain a reaction mixture; BPTME (10.6886 g, 20.0 mmol) and BPDA (8.8266 g, 30.0 mmol) were added to the mixture. ) and NMP (64.2 g) were added to the reaction mixture to obtain a polymerization system with a solid content of 25 wt%. After 1 h, when the initial heat of polymerization was released, the cold bath was removed and the reaction temperature naturally rose to room temperature. After 12 h, a uniform, transparent and viscous light brown PAA solution was obtained. The polymerization reaction was continued at room temperature for 24 h, and NMP (92.6 g) was added to dilute the PAA solution to 15 wt%. The PAA solution was filtered through a 0.45 μm Teflon syringe and the obtained PAA solution was stored in a refrigerator at -18°C.
[0060] (2) Same as step (2) of Example 1.
[0061] Comparative Example 1 Fluorine-containing thermoplastic polyester imide film
[0062] (1) Add 4-aminophenyl 4-aminobenzoate (APAB, 3.6520 g, 16.0 mmol), 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFMB, 7.6855 g, 24.0 mmol) and NMP (40.0 g) to a 250 mL three-necked glass bottle equipped with a mechanical stirrer, nitrogen inlet and outlet tubes, and a cold water bath; cool the reaction vessel to 10° C. using circulating cold water, and fill the three-necked glass bottle with dry nitrogen. After stirring for 30 minutes, APAB and TFMB are completely dissolved in the solvent to obtain a reaction mixture; add bisphenol A diether dianhydride (TMBPA, 11.5302 g, 20.0 mmol), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 5.8844 g, 20.0 mmol) and NMP (46.3 g) were added to the reaction mixture to obtain a polymerization system with a solid content of 25 wt%. After 1 hour, when the initial heat of polymerization was released, the cold bath was removed, and the reaction temperature naturally rose to room temperature. After 12 hours, a uniform, transparent and viscous light brown PAA solution was obtained. The polymerization reaction was continued at room temperature for 24 hours, and NMP (76.6 g) was added to dilute the PAA solution to 15 wt%. The PAA solution was filtered through a 0.45 μm Teflon syringe, and the obtained PAA solution was stored in a refrigerator at -18°C;
[0063] (2) Same as step (2) of Example 1.
[0064] Comparative Example 2 Fluorine-containing thermoplastic polyester imide film
[0065] (1) Add 4-aminophenyl 4-aminobenzoate (APAB, 3.6520 g, 16.0 mmol), 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFMB, 7.6855 g, 24.0 mmol) and NMP (40.0 g) to a 250 mL three-necked glass bottle equipped with a mechanical stirrer, nitrogen inlet and outlet tubes, and a cold water bath; cool the reaction vessel to 10° C. using circulating cold water, and fill the three-necked glass bottle with dry nitrogen. After stirring for 30 minutes, APAB and TFMB are completely dissolved in the solvent to obtain a reaction mixture; add bisphenol A diether dianhydride (TMBPA, 9.2242 g, 16.0 mmol), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 7.0613 g, 24.0 mmol) and NMP (42.9 g) were added to the reaction mixture to obtain a polymerization system with a solid content of 25 wt%. After 1 h, when the initial heat of polymerization was released, the cold bath was removed, and the reaction temperature naturally rose to room temperature. After 12 h, a uniform, transparent and viscous light brown PAA solution was obtained. The polymerization reaction was continued at room temperature for 24 h, and NMP (73.6 g) was added to dilute the PAA solution to 15 wt%. The PAA solution was filtered through a 0.45 μm Teflon syringe, and the obtained PAA solution was stored in a refrigerator at -18°C;
[0066] (2) Same as step (2) of Example 1.
[0067] Comparative Example 3
[0068] The difference from Example 2 is that ABABP is replaced by an equal molar amount of bis(4-aminophenyl)terephthalate (BAPT), that is, the preparation method is:
[0069] (1) BAPT (17.4175 g, 50.0 mmol) and NMP (40.0 g) were added to a 250 mL three-necked glass bottle equipped with a mechanical stirrer, nitrogen inlet and outlet tubes, and a cold water bath; the reaction vessel was cooled to 10° C. using circulating cold water, and dry nitrogen was filled into the three-necked glass bottle. After stirring for 30 minutes, ABABP was completely dissolved in the solvent to obtain a reaction mixture; BPTME (2.6722 g, 5.0 mmol) and BPDA (13.2399 g, 45.0 mmol) were mixed with N MP (60.0 g) was added to the reaction mixture to obtain a polymerization system with a solid content of 25 wt%. After 1 h, when the initial heat of polymerization was released, the cold bath was removed and the reaction temperature naturally rose to room temperature. After 12 h, a uniform, transparent and viscous light brown PAA solution was obtained. The polymerization reaction was continued at room temperature for 24 h, and additional NMP (88.9 g) was added to dilute the PAA solution to 15 wt%. The PAA solution was filtered through a 0.45 μm Teflon syringe and the obtained PAA solution was stored in a refrigerator at -18 °C.
[0070] (2) Same as step (2) of Example 1.
[0071] Comparative Example 4
[0072] The difference from Example 2 is that BPTME is replaced by an equimolar amount of p-phenylene-diphenyltrimethylol dianhydride (TAHQ), that is, the preparation method is:
[0073] (1) ABABP (15.2170 g, 50.0 mmol) and NMP (40.0 g) were added to a 250 mL three-necked glass bottle equipped with a mechanical stirrer, nitrogen inlet and outlet tubes, and a cold water bath; the reaction vessel was cooled to 10° C. using circulating cold water, and dry nitrogen was filled into the three-necked glass bottle. After stirring for 30 minutes, ABABP was completely dissolved in the solvent to obtain a reaction mixture; TAHQ (2.2916 g, 5.0 mmol) and BPDA (13.2399 g, 45.0 mmol) were mixed with N MP (52.2 g) was added to the reaction mixture to obtain a polymerization system with a solid content of 25 wt%. After 1 h, when the initial heat of polymerization was released, the cold bath was removed and the reaction temperature naturally rose to room temperature. After 12 h, a uniform, transparent and viscous light brown PAA solution was obtained. The polymerization reaction was continued at room temperature for 24 h, and additional NMP (82.0 g) was added to dilute the PAA solution to 15 wt%. The PAA solution was filtered through a 0.45 μm Teflon syringe and the obtained PAA solution was stored in a refrigerator at -18 °C.
[0074] (2) Same as step (2) of Example 1.
[0075] Performance Test:
[0076] 1. Thermal performance evaluation:
[0077] 1.1. Dynamic Mechanical Analysis (DMA): The films obtained in Examples 1-5 and Comparative Examples 1-4 were tested on a TA Q800 thermal analysis system at a heating rate of 5°C / min and a frequency of 1 Hz in nitrogen. This test can obtain the glass transition temperature (Tg) data of the film, and the results are shown in Table 1;
[0078] Meanwhile, it can be known from the test that the fluorine-free thermoplastic polyesterimide film prepared by the present invention has good thermoplasticity.
[0079] 1.2. Thermomechanical analysis (TMA): The films obtained in Examples 1-5 and Comparative Examples 1-4 were tested on a Netzsch TMA402F3 thermal analysis system at a heating rate of 5°C / min in a nitrogen atmosphere. This test can obtain the linear thermal expansion coefficient (CTE) data of the film, and the results are shown in Table 1;
[0080] 1.3. Thermogravimetric analysis (TGA) and corresponding derivative TGA (DTG): The films obtained in Examples 1-5 and Comparative Examples 1-4 were tested on a Netzsch TG 209F3 thermogravimetric analyzer at a heating rate of 20°C / min in a nitrogen atmosphere. This test can obtain the 5% weight loss temperature (T 5% ), the temperature at which the first and second fastest thermal decomposition occurs (T max1 , T max2 ) and the residual weight ratio (R w750 ) data, and the results are shown in Table 1.
[0081] 2. Dielectric property evaluation: Silver electrodes were made on both sides of the films obtained in Examples 1-5 and Comparative Examples 1-4, respectively. The films were pre-dried at 100°C for 1 h using conductive silver paint and then precisely cut into small pieces (1 cm × 1 cm × 3 mm). The dielectric constant (D k ) and dielectric loss (D f ) The data were recorded as the average value of 5 parallel samples and the results are shown in Table 1.
[0082] Table 1
[0083]
[0084] It can be seen from Table 1 that compared with the fluorine-containing thermoplastic polyester imide films prepared with TMBPA, BPDA, APAB and TFMB in Comparative Examples 1 and 2, the biphenyl bridged thermoplastic polyester imide films prepared with BPTME, BPDA and PAPAB in Examples 1-5 are fluorine-free and maintain low D k and D f In the case of , it also has a CTE that is more matched with the copper foil, better high temperature dimensional stability, and lower Tg; compared with Comparative Example 3 in which ABABP in Example 2 is replaced with an equal molar amount of bis(4-aminophenyl)terephthalate (BAPT), Examples 1-5 have better high temperature dimensional stability and thermoplasticity, lower D k , D f , CTE; compared with Comparative Example 4 in which BPTME in Example 2 is replaced with an equal molar amount of p-phenylene-trimethylene dianhydride (TAHQ), Examples 1-5 have better high temperature dimensional stability and a CTE that is more compatible with copper foil.
[0085] It can be seen that the biphenyl bridge thermoplastic polyester imide film material provided by the present invention has excellent comprehensive properties without using fluorine-containing materials, including excellent thermoplasticity, high temperature dimensional stability, dielectric properties, and CTE that is more matched with the CTE of copper foil, etc., and the preparation process is simple to operate, the reaction is controllable, and the reaction product is adjustable. This implementation scheme has good industrial prospects in two-layer FCCL at high frequencies.
[0086] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A biphenyl bridged thermoplastic polyester imide, characterized in that: It is prepared by polymerization of biphenyl dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, 3,3',4,4',-biphenyltetracarboxylic dianhydride and 2-(4-aminobenzoate)-5-aminobiphenyl; the structural formula is shown in formula (I): (I); wherein m represents the mole number of biphenyl dibenzoate-3,3',4,4',-tetracarboxylic dianhydride, m is an integer from 0 to 100, and m may be 0; n represents the mole number of 3,3',4,4',-biphenyltetracarboxylic dianhydride, n is an integer from 0 to 100, and n is not 0.
2. The biphenyl bridged thermoplastic polyester imide according to claim 1, characterized in that: The ratio of m to n is 0-40:60-100.
3. The method for preparing the biphenyl bridged thermoplastic polyester imide according to claim 1 or 2, characterized in that: The following steps are involved: (1) Under nitrogen protection, biphenyl dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride and 2-(4-aminobenzoate)-5-aminobiphenyl undergo polymerization reaction in a solvent to obtain a polyamic acid solution; (2) The polyamic acid solution is subjected to thermal imidization to obtain biphenyl bridged thermoplastic polyester imide.
4. The preparation method according to claim 3, characterized in that: The total molar ratio of the 2-(4-aminobenzoate)-5-aminobiphenyl to biphenyl dibenzoate-3,3',4,4'-tetracarboxylic dianhydride and 3,3',4,4',-biphenyltetracarboxylic dianhydride is 1:0.9-1.
1.
5. The preparation method according to claim 4, characterized in that: The thermal imidization adopts programmed temperature rise, and the programmed temperature rise steps are: 70-90°C for 0.5-1.5h, 110-130°C for 0.5-1.5h, 140-160°C for 0.5-1.5h, 170-190°C for 0.5-1.5h, 240-260°C for 0.5-1.5h, and 290-310°C for 0.5-1.5h.
6. The preparation method according to claim 5, characterized in that: The solvent is selected from at least one of anhydrous N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide and dimethyl sulfoxide.
7. The preparation method according to claim 6, characterized in that: The polymerization reaction is carried out at 5°C-35°C, and the reaction time is 20h-30h.
8. A biphenyl bridged thermoplastic polyester imide film, characterized in that: The composition comprises the biphenyl bridged thermoplastic polyester imide of claim 1 or 2.
9. The biphenyl bridged thermoplastic polyester imide film according to claim 8, characterized in that: The biphenyl bridge thermoplastic polyester imide film has a thickness of 0.03-0.05 mm and a linear thermal expansion coefficient of <26×10 -6 / K, glass transition temperature ≥230℃, dielectric constant <3.6, dielectric loss ≤0.
005.
10. Use of the biphenyl bridged thermoplastic polyester imide according to claim 1 or 2 or the biphenyl bridged thermoplastic polyester imide film according to any one of claims 8 to 9 in the preparation of a two-layer flexible copper clad laminate.
Citation Information
Patent Citations
Polyimide composition, polyimide, flexible copper clad laminate and its manufacturing method
CN111484616B
A low dielectric blended polyimide and its preparation method and application
CN115850699B
Diamine compound, and polyimide compound and molded article in which said diamine compound is used
CN110198926A